Information Processing Under Reward Versus Under Punishment. (May 2019) - Ballard, Timothy; Sewell, David K.; Cosgrove, Daniel; Neal, Andrew
Much is known about the effects of reward and punishment on behavior, yet little research has considered how these incentives influence the information-processing dynamics that underlie decision making. We fitted the linear ballistic accumulator to data from a perceptual-judgment task to examine the impacts of reward- and punishment-based incentives on three distinct components of information processing: the quality of the information processed, the quantity of that information, and the decision threshold. The threat of punishment lowered the average quality and quantity of information processed, compared with the prospect of reward or no performance incentive at all. The threat of punishment also induced less cautious decision making by lowering people's decision thresholds relative to the prospect of reward. These findings suggest that information-processing dynamics are determined not only by objective properties of the decision environment but also by the higher order goals of the system.